Flickering Lights and Declaiming Bodies: Semiosis in Film and Theatre - Nunn, Robert (Theatre Research in Canada / Recherches théâtrales au Canada, 1996)
Of all the elements that mark the boundary between theatre and film, presence seems to be the most important. This essay seeks to set aside a sterile debate about whether presence renders theatre innately superior or inferior to film, and instead examines how presence in theatre and absence in film function as elements in the process of making meaning, arguing that it is presence which is the condition for theatrical semiosis, the material support for the kinds of meaning-making that constitute theatre, and, conversely, absence which is the condition for the specific kind of semiosis characteristic of film. After comparing how objects signify on stage and in film, the essay seeks to clarify the difference between acting on stage and in film by drawing on Eugenio Barba’s distinction between daily and extra-daily behaviour. De tous les éléments qui distinguent le cinéma du théâtre, c’est la présence qui semble être le plus important. Cet article cherche à mettre de côté un débat stérile sur la supériorité ou infériorité du théâtre par rapport au cinéma en raison de la présence, pour examiner la manière dont la présence au théâtre et l’absence au cinéma fonctionnent comme des éléments constitutifs du sens. Nous montrons que c’est la présence qui est la condition pour la sémiosis théâtrale, et, inversement, l’absence qui est la condition pour la sémiosis caractéristique du cinéma. Après avoir comparé la façon dont les objets signifient sur scène et à l’ecran, cet essai cherche à clarifier la différence entre le travail de l’acteur au théâtre et au cinéma en faisant appel à la distinction d’Eugenio Barba entre la gestualité quotidienne et la gestualité de représentation.